Nicotinamide, a Poly [ADP-Ribose] Polymerase 1 (PARP-1) Inhibitor, as an Adjunctive Therapy for the Treatment of Alzheimer’s Disease - Salech, Felipe; Ponce, Daniela P.; Paula-Lima, Andrea C.; SanMartin, Carol D.; Behrens, María I. (Frontiers in Aging Neuroscience, 2020)
Nicotinamide (vitamin B3) is a key component in the cellular production of Nicotinamide Adenine Dinucleotide (NAD) and has long been associated with neuronal development, survival and death. Numerous data suggest that nicotinamide may offer therapeutic benefits in neurodegenerative disorders, including Alzheimer’s Disease (AD). Interestingly, nicotinamide is an inhibitor of Poly [ADP-ribose] polymerase 1 (PARP-1), a nuclear DNA repair enzyme that under intense DNA damage depletes the cell of NAD+ and ATP, and leads to a non-apoptotic type of cell death called Parthanatos, which has been associated with the pathogenesis of neurodegenerative diseases. Here we discuss the evidence supporting the use of nicotinamide as adjunctive therapy for the treatment of early stages of AD based on the inhibitory effect of nicotinamide on PARP-1 activity. We have previously reported in human lymphocytes that PARP-1 inhibition with nicotinamide and 3-aminobenzamide (3-ABA) protects against oxidative death induced by hydrogen peroxide. Interestingly, PARP-1 inhibition almost completely protects lymphocyte death from mild cognitive impairment (MCI) but not AD patients, suggesting there might be a therapeutic window at initial stages of neurodegeneration. PARP-1 inhibition may also exert a protective effect against neurodegeneration by its action to diminish neuroinflammation and microglial activation which also are implicated in the pathogenesis of AD. These data support evaluating nicotinamide as an adjunctive treatment for AD at early stages of the disease and raise the hypothesis that other PARP-1 inhibitors –drugs that are already approved for breast cancer treatment– might be explored for the treatment of AD.